Desarrollo de un sistema gráfico de museografía para el museo de Ciencias Naturales de la Universidad Nacional De Chimborazo - Cuji Miranda, Luis Marcelo (2018)
Nowdays, the graphic designer is immersed in all social backround solving the problems of visual character, through the use of iconic, linguistic and chromatic codes, which must possess each elaborated desing. At the Universidad Nacional of Chimborazo, the Faculty of Sciences of Human Education and Technologies of the Chemical Biology and Laboratory majors is located in the museum of natural sciences, in this place there are a loto f disadvantages for users, such as lack of signs in the different exhibition sitas and the information of the existing species in the place. That is why the decision to create a signage and informing the people who attend to the museum, but these systems are prepared under the methodology of Robert Scott, this made up of 4 reasons, they have been developed by performing the corresponding analysis. We Will also use a variety of instuments for the managment of this Project.